Adsorption process on fixed bed column in rich organic wastewater treatment experimental studies and numerical simulation - Khanh, Nguyen Hong; Hoang, Nguyen Viet (Vietnam Journal of Mechanics, 2006)
None axially dispersed plug flow model (NADPF) was applied to simulate adsorption process on fixed bed column. To determine model input parameters and verify the model, isotherm curve, solid diffusion coefficient (\(D_s\)) and breakthrough curve have been determined from experiment. Activated carbon SWW 210&220 was selected as the main adsorbent for research. Wastewater of Minhkhai Textile Company is the sample used in experiment study. According to isotherm function, textile wastewater is poorly adsorbed into SWW210&220. Kinetic data also show that diffusion step of textile wastewater is very slow (DS ~ 1.31*\(10^{-13}\) m\(^2\)/s). With textile wastewater, NADPF model can be used to simulate adsorption process.